2013
DOI: 10.1016/j.febslet.2013.05.056
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of phenol‐induced changes in lipid composition on conformation of OmpF‐like porin of Yersinia pseudotuberculosis

Abstract: a b s t r a c tThe present work aimed to compare the effects of different lysophosphatidylethanolamine (LPE) content in lipids derived from Yersinia pseudotuberculosis cells exposed and not exposed to phenol on the conformation of OmpF-like porin of these bacteria. Differential scanning calorimetry and intrinsic protein fluorescence showed that the 2.5-fold increase of LPE content and the corresponding increase in the phase transition temperature of bacterial lipids were accompanied by enhanced protein thermos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Although the content of lysophospholipids is small, they are essential components of bacterial cell membranes. The change of lysophospholipid content could affect the spontaneous curvature of cell membrane and the conformation of ion channel [67]. LPE contents increased in S. putrefaciens cultivated at lower temperature, coinciding with the study results of Nina et al that the environmental stress led to a significant increase in the content of LPE in Yersinia pseudotuberculosis [68].…”
Section: Changes In Lipids Contentsupporting
confidence: 86%
“…Although the content of lysophospholipids is small, they are essential components of bacterial cell membranes. The change of lysophospholipid content could affect the spontaneous curvature of cell membrane and the conformation of ion channel [67]. LPE contents increased in S. putrefaciens cultivated at lower temperature, coinciding with the study results of Nina et al that the environmental stress led to a significant increase in the content of LPE in Yersinia pseudotuberculosis [68].…”
Section: Changes In Lipids Contentsupporting
confidence: 86%
“…It was suggested that phenol could interact with bacteria/fungi, leading to saturation of the phospholipid bilayers in the cell membrane and protein conformation transition, which could cause membrane perturbation and microbial cell lysis. 25,26 It is also possible that the phenol groups could form phenoxyl radicals 27 that are stabilized by the aromatic ring. The radicals would stimulate stress, resulting in microbial cell lysis and nucleic acid leakage.…”
Section: Antimicrobial and Biofilm-controlling Functionsmentioning
confidence: 99%
“…As an ectothermic organism, Y. pseudotuberculosis changes its own lipid profile depending on the cultivation conditions. In particular, the availability of glucose in nutrition broth, increased temperature, anaerobic conditions, or phenol biocide result in the accumulation of a remarkable amount of lysophosphatidylethanolamine (LPE) mainly in the OM [Bakholdina et al, 2004;Sanina et al, 2013;Davydova et al, 2016]. These adaptive changes significantly influence the conformation of the major OM protein OmpF that may hinder transport of the various lowmolecular substances, including β-lactam antibiotics, through the OM [Sanina et al, 2013].…”
mentioning
confidence: 99%
“…In particular, the availability of glucose in nutrition broth, increased temperature, anaerobic conditions, or phenol biocide result in the accumulation of a remarkable amount of lysophosphatidylethanolamine (LPE) mainly in the OM [Bakholdina et al, 2004;Sanina et al, 2013;Davydova et al, 2016]. These adaptive changes significantly influence the conformation of the major OM protein OmpF that may hinder transport of the various lowmolecular substances, including β-lactam antibiotics, through the OM [Sanina et al, 2013]. Differential scanning calorimetry and intrinsic protein fluorescence demonstrated that the increase of LPE content and the corresponding increase in the phase transition temperature of bacterial lipids was accompanied by enhanced trimeric OmpF protein thermal stability.…”
mentioning
confidence: 99%